INVENTARISASI DURIAN UNGGUL LOKAL (Durio zibenthinus Murr.) DI RANCAMAYA KEC. BOGOR SELATAN, KOTA BOGOR, JAWA BARAT, INDONESIA - Sumanto (UIN Sunan Gunung Djati Bandung, 2023)
Durian (Durio zibenthinus Murr.) is a tropical fruit-producing plants in Southeast Asia known as the king of fruit and its become a cultivated plant. Rancamaya Village included in the South Bogor District area, its known as the location for producing local Bogor typical durian, with a unique taste and different from other types. The purpose of this study was to obtain information related to the number and varieties of local superior durian based on several morphological characters, namely the weight of each fruit, the physical shape of the fruit, the thickness of the flesh per fruit, the smell and taste of the fruit, and the number of fruits per year/tree. It was carried out from January 2019 to September 2019. The method used was an exploratory method, namely visiting the location of the durian plants growing and based on a field survey found 12 superior local durians.